2019
DOI: 10.1242/jcs.223230
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia suppresses myofibroblast differentiation by changing RhoA activity

Abstract: Fibroblasts show a high range of phenotypic plasticity, including transdifferentiation into myofibroblasts. Myofibroblasts are responsible for generation of the contraction forces that are important for wound healing and scar formation. Overactive myofibroblasts, by contrast, are involved in abnormal scarring. Cell stretching and extracellular signals such as transforming growth factor β can induce the myofibroblastic program, whereas microenvironmental conditions such as reduced tissue oxygenation have an inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…This system involves the participation of inner plasma membrane proteins associated with Ror1/2 that control cell polarity and asymmetric cell division through the regulation of actin filament organization by the action of the small GTPases RhoA and Rac 31, 32 . Our work is consistent with other studies that have implicated planar cell polarity proteins in myofibroblast differentiation, including the reported induction of Frizzled2 in myofibroblasts after experimental myocardial infarction 64 and hypoxia-mediated suppression of myofibroblast differentiation through RhoA inhibition 65 . Furthermore, ablation of Smad3, a key signaling protein downstream of TGF-β cardiac fibroblasts 66 , will lead to the suppression of RhoA and a disruption of actin alignment 57 .…”
Section: Discussionsupporting
confidence: 92%
“…This system involves the participation of inner plasma membrane proteins associated with Ror1/2 that control cell polarity and asymmetric cell division through the regulation of actin filament organization by the action of the small GTPases RhoA and Rac 31, 32 . Our work is consistent with other studies that have implicated planar cell polarity proteins in myofibroblast differentiation, including the reported induction of Frizzled2 in myofibroblasts after experimental myocardial infarction 64 and hypoxia-mediated suppression of myofibroblast differentiation through RhoA inhibition 65 . Furthermore, ablation of Smad3, a key signaling protein downstream of TGF-β cardiac fibroblasts 66 , will lead to the suppression of RhoA and a disruption of actin alignment 57 .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Solodushko et al 46 showed that when rat and human pulmonary microvascular endothelial cells were cultured in 5% O 2 compared to 21% O 2 they formed tighter junctions and were less permeable due to a reduction in RhoA-GTPase activity. Recently, Leinhos et al 47 showed that Rho-GTPase activity was markedly downregulated in fibroblasts exposed to 1% oxygen. Rho-GTPases are regulated by GEFs (guanine exchange factors) that promote exchange of GDP for GTP and activate Rho proteins, and by GAPs (guanine activating factors) that facilitate the exchange of GTP for GDP that turn off the activity of Rho proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Rho-GTPases are regulated by GEFs (guanine exchange factors) that promote exchange of GDP for GTP and activate Rho proteins, and by GAPs (guanine activating factors) that facilitate the exchange of GTP for GDP that turn off the activity of Rho proteins. Reduced activity of RhoA was attributed to a selective induction in GAP ARHGAP29 expression under hypoxia 47 . It is possible that under our prolonged and severe hypoxic conditions (14 h at 0.1 or 1% O 2 ), or under conditions of total energy depletion, a GAP protein(s) was induced, which may have contributed to the reduction in Rho-GTPase activity we reported here.…”
Section: Discussionmentioning
confidence: 99%
“…surrounding vasculature) and vital in the regulation of tissue remodeling and homeostasis. The BMP7+ population had genes involved in myofibroblast differentiation, epithelial mesenchymal transition (EMT) and in TGFβ1-WNT signaling (PRSS23, ITGA8, BMP7, ITM2A and ARHGAP29) (15)(16)(17)(18). We hypothesize these three stromal clusters (ACTA+, ECM and BMP7+) represent stromal subtypes active in ECM breakdown, remodeling and organization which are important processes during proliferation, tissue repair and regeneration occurring in the endometrium, during, and after menstruation.…”
Section: Heterogeneity In the Endometrial Stromal Compartment And Posmentioning
confidence: 99%